En sammenhængende overgang? Om legens fleksible deltagelsesrum i overgangen fra dagtilbud til skole - Odgaard, Ane Bjerre; Koch, Anette Boye; Skovbjerg, Helle Marie (Tidsskrift for Professionsstudier, 2023)
This paper examines play experiments during children’s transition from kindergarten to school. Empirically, the article relies on field observations from a pilot study in 2020 where play experiments were designed and unfolded as transition activities in a Danish school district. In a range of pedagogically framed play experiments at the local school, the oldest children from the local kindergartens participated together with school children from 3rd grade, and with pedagogical professionals from kindergartens and school. The play experiments are examined by shedding light the children’s pathways to school as they unfold in these activities, as well as by highlighting what potentials this activity format displays with regards to coherence during transition to school. A central finding is that the play experiments enable pathways into the school as a flexible participatory space. However, this poses different demands on the professionals’ participation than many other transition activities. The play experiments actualize transition as a process where readiness cannot be assigned to either the child, the kindergarten, or the school. Rather, all participants must mutually adjust to one another within the framing of play orders.